Bibliometric Analysis of Islamic Business Model to Explore the Determinants of Customer Satisfaction - Sari, Dia Purnama; Cahyani, Utari Evy; Aviva, Itsla Yunisva; Siregar, Rizal Ma'ruf Amidy (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2022)
This study aims to provide a bibliometric analysis of the Islamic business model. This study presents bibliometric analysis and identifies publication trends within the scope of the Islamic business model in journals indexed by the dimensions database from 1994 to 2022. This study uses descriptive statistics based on 217 published articles related to the Islamic business model. The data was collected from the dimensions database and analyzed using VOSviewer. The results showed that most articles on Islamic business models were published in 2021. The journals that contain the most articles on Islamic business models are the